Noniterative density functional response approach: application to nonlinear optical properties of p-nitroaniline and its methyl-substituted derivatives - Sophy, K. B.; Shedge, Sapana V.; Pal, Sourav (Journal of Physical Chemistry A, 2008)
We report the effect of substitution, position of the substituent, and the symmetry on the nonlinear optical properties of p-nitroanline (PNA) and its derivatives using our implementation of the noniterative approximation of couple-perturbed Kohn-Sham (CPKS) equation in the deMon2k. Dipole moment, static polarizability, and first hyperpolarizability of these pi-conjugated donor-acceptor organic derivatives of PNA and its methyl-substituted analogs are calculated using our method at different exchange correlation functionals, namely, BP86, BPW91, and BLYP, using 6-31++G** basis set. A comparison of results obtained by our method with those obtained by MP2 (finite-field perturbation) method is presented in this paper. The effect of optical gap on charge transfer and subsequently on polarizabilities has been illustrated.

Comparison of the auxiliary density perturbation theory and the noniterative approximation to the coupled perturbed kohn-sham method: case study of the polarizabilities of disubstituted azoarene molecules - Shedge, Sapana V.; Carmona-Espindola, Javier; Pal, Sourav; Koster, Andreas M. (Journal of Physical Chemistry A, 2010)
We present a theoretical study of the polarizabilities of free and disubstituted azoarenes employing auxiliary density perturbation theory (ADPT) and the noniterative approximation to the coupled perturbed Kohn-Sham (NIA-CPKS) method. Both methods are noniterative but use different approaches to obtain the perturbed density matrix. NIA-CPKS is different froth the conventional CPKS approach in that the perturbed Kohn-Sham matrix is obtained numerically, thereby yielding a single-step solution to CPKS. ADPT is an alternative approach to the analytical CPKS method in the framework of the auxiliary density functional theory. It is shown that the polarizabilities obtained using these two methods are in good agreement with each other. Comparisons are made for disubstituted azoarenes, which give support to the push-pull mechanism. Both methods reproduce the same trend for polarizabilities because of the substitution pattern of the azoarene moiety. Our results are consistent with the standard organic chemistry ``activating/deactivating'' sequence. We present the polarizabilities of the above molecules calculated with three different exchange-correlation functionals and two different auxiliary function sets. The computational advantages of both methods are also discussed.

Validation and application of auxiliary density perturbation theory and non-iterative approximation to coupled-perturbed Kohn-Sham approach for calculation of dipole-quadrupole polarizability - Shedge, Sapana V.; Pal, Sourav; Koester, Andreas M. (Chemical Physics Letters, 2011)
Recently, two non-iterative approaches have been proposed to calculate response properties within density functional theory (DFT). These approaches are auxiliary density perturbation theory (ADPT) and the non-iterative approach to the coupled-perturbed Kohn-Sham (NIA-CPKS) method. Though both methods are non-iterative, they use different techniques to obtain the perturbed Kohn-Sham matrix. In this Letter, for the first time, both of these two independent methods have been used for the calculation of dipole-quadrupole polarizabilities. To validate these methods, three tetrahedral molecules viz., P-4; CH4 and adamantane (C10H16) have been used as examples. The comparison with MP2 and CCSD proves the reliability of the methodology. (C) 2011 Elsevier B. V. All rights reserved.

Behaviour of density functional theory for electric response properties at distorted geometries of molecules - Shedge, Sapana V.; Joshi, Sayali P.; Pal, Sourav (Theoretical Chemistry Accounts, 2012)
The role of exchange-correlation is well known for accurate calculations of electric response properties. The exchange-correlation functional in density functional theory (DFT) has been well studied for ground state equilibrium geometry. However, the behaviour of these functional in stretched geometries, where static correlation play an important role, has not been studied systematically, particularly for response electric properties. Thus, we present here the rigorous calculation of electric response properties at distorted geometries of the molecules. We have considered dipole polarizability and dipole-quadrupole polarizability for description of role of static and dynamic correlation for electric response properties. The calculations are performed with our new approach, noniterative approximation to coupled-perturbed Kohn-Sham method. These DFT results are compared with higher level ab initio such as coupled perturbed singles and doubles and fully correlated full CI. We have studied single, double and triple-bonded systems at different inter-nuclear separation. We report here the dipole polarizability and dipole-quadrupole polarizability of HF, BH, H2CO, CO and NO+. We also present the effect of basis and functional on polarizability and dipole-quadrupole polarizability.
Keywords: DFT; Dipole-dipole polarizability; Dipole-quadrupole polarizability; Distorted geometry; NIA-CPKS

Theoretical study of frequency and temperature dependence of dipole-quadrupole polarizability of P-4 and adamantane - Shedge, Sapana V.; Pal, Sourav; Koester, Andreas M. (Chemical Physics Letters, 2012)
The frequency and temperature dependence of dipole-quadrupole polarizability of tetrahedral P-4 and adamantane molecules have been studied using first-principle all-electron density functional theory calculation. The recently developed time-dependent auxiliary density functional theory is extended for the calculation of dynamic dipole-quadrupole polarizabilities. Temperature effects are incorporated by Born-Oppenheimer molecular dynamics (BOMD) simulations recorded up to 100 ps. The dynamic dipole-quadrupole polarizabilities are calculated along these trajectories. The frequency and temperature effects can be significant for the accurate calculation of dipole-quadrupole polarizability. We have also identified the main reason for the observed discrepancy between experiment and theory in the case of adamantane. (c) 2012 Elsevier B.V. All rights reserved.